“Publica(c)tion”: E. Pauline Johnson’s Publishing Venues and their Contemporary Significance - Milz, Sabine (Studies in Canadian Literature, 2004)
By combining Aboriginal storytelling, European performance entertainment, and the printed word, E. Pauline Johnson’s practice of publica(c)tion challenged and still challenges the prevalent Eurocentric notion of Canadian literature as a literature that is created, published, and consumed in print. She could not be stopped in her career as a storyteller-writer-performer when she encountered the financial and material obstacles of print publication, which she circumvented by reverting to alternative modes. In the stage performance of her Victorian Romantic poetry, the dramatization of her short stories, and the wearing of costumes that catered to both elite and popular tastes, she crossed the boundaries of "high" and "low" literature, written and oral communication.